Hubungan Kepercayaan Diri dengan Komunikasi Interpersonal pada Mahasiswa Rantau - Natania, Luisa; Roswiyani, Roswiyani (Peneliti.net, 2023)
The lack of dissemination of the quality of tertiary institutions in Indonesia is one of the reasons students decide to go abroad. As an overseas university student, of course, you need adjustments and changes when you enter the world of university. One of the important aspects that must be owned by an overseas university student is self-confidence. Self-confidence is important for a student, especially overseas university students, so that it can influence effective interpersonal communication. Interpersonal communication is important for an overseas university student to have in order to increase positive behavior and develop social skills. However, in reality, there are still students who lack confidence and have fear in communicating. The purpose of this study was to determine the relationship between self-confidence and interpersonal communication among overseas university students. This research involved 202 overseas university students with an age range of 18-25 years. The measurement tools used are the self-confidence scale from Lauster (1992) which has been used in the research of Nuraeni (2010) and the interpersonal communication scale from DeVito (1997) which has been used in the research of Putri (2014). The results obtained in this study are that there is a positive relationship between self-confidence and interpersonal communication with the result r = .665. Therefore, it can be concluded that the higher the self-confidence, the higher the interpersonal communication will be. Vice versa, the lower the self-confidence, the lower the interpersonal communication will be.